Feminism, nationalism, and labour in post-civil war Northern Province of Sri Lanka. Issue 1 (2nd January 2017) - Sarvananthan, Muttukrishna; Suresh, Jeyapraba; Alagarajah, Anushani
ABSTRACT: This viewpoint highlights the paradox of low labour force participation and high unemployment among women at a time of growing educational levels of women in the former conflict-affected Northern Province of Sri Lanka. It highlights the rise of ethno-feminism and sub-nationalism that undermine what few opportunities open up for women in terms of employment and livelihood opportunities, thereby weakening the peacebuilding efforts of various stakeholders.